(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
From a young age, Momaday was deeply immersed in the Kiowa culture of his paternal lineage. Momaday's writing possesses a poetic quality mostly due to his background as a poet and storyteller. House Made of Dawn achieved immediate acclaim, winning the Pulitzer Prize in 1969, a year post-publication, which facilitated the emergence of numerous Native authors, nearly all of whom attribute their success to Momaday, including James Welch, Leslie Marmon Silko, Gerald Vizenor, Louise Erdrich, and Sherman Alexie. Silko, akin to Louise Erdrich, explores the issue of hybrid identity in her writings, particularly focussing on the sensation of being “neither white nor entirely traditional Indian.” In 1977, Silko published her inaugural novel, Ceremony; it serves as a reaction from the Laguna people to N. Scott Momaday's Pulitzer Prize-winning work, House Made of Dawn. This study seeks to analyse the theme of identity through the interconnected elements of identification, home, ritual, and narrative in N. Scott Momaday's House Made of Dawn and Leslie Marmon Silko's Ceremony. Abel and Tayo's return home channels the solitary energies of individuals into the collective, enabling characters to return to their respective homes. Abel and Tayo's wartime traumas have estranged them to such an extent that they are incapable of recognising their environment or possessing a coherent sense of self. The author analyses several features that establish a sense of “home” for the characters, as well as the methods by which they have been “unhomed.” The paper through the selected works examines how the indigenous consciousness compelled the Natives to restore their identity.